Konflik Normatif Antara Non-Refoulement Dan Kedaulatan Negara: Tinjauan Filosofis Dan Hukum Dalam Kasus Pengungsi Rohingya Dari Bangladesh - Putri, Nabila Riana; Natamiharja, Rudi; Sujadmiko, Bayu (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
State sovereignty as the exclusive right to regulate domestic affairs often clashes with international obligations to respect the principle of non-refoulement in refugee protection, especially Rohingya refugees. The conflict between sovereignty and international legal obligations poses a complex normative dilemma, where the state must balance national interests, security, and the protection of human rights. Restrictions on the application of the principle of non-refoulement can be done proportionally and in accordance with international legal norms and universal moral principles in natural law theory. International cooperation and strengthening domestic laws are key in managing such restrictions so as not to violate refugee rights. With a wise and harmonious approach, states can ensure the protection of refugees without compromising national stability, security and sovereignty, thus creating a more responsive and humane international legal system.